The Association Between Long-Term Acenocoumarol Treatment and Vitamin D Deficiency - Sawicka-Powierza, Jolanta; Konstantynowicz, Jerzy; Jablonska, Ewa; Zelazowska-Rutkowska, Beata; Jelski, Wojciech; Abramowicz, Pawel; Sasinowski, Caroline; Chlabicz, Slawomir (Frontiers in Endocrinology, 2018)
Objective Both vitamin D and K2 are involved in a number of metabolic processes, including bone metabolism; however, associations between the vitamins are not fully understood. The aim of the study was to evaluate serum concentrations of 25-hydroxyvitamin D [25(OH)D] in adult patients receiving long-term acenocoumarol (AC) treatment. Participants and methods In this cross-sectional study, 58 Caucasian patients (31 women, 27 men) with a median age of 65 years receiving long-term AC therapy were evaluated and compared with 35 age- and gender-matched healthy controls. The AC treatment was used due to recurrent venous thromboembolism (34.5%), atrial fibrillation (31%), or mechanical heart valve prostheses (34.5%). Medical records and a questionnaire were used to obtain information about chronic diseases, smoking habits, and the duration of therapy and weekly dose of AC. Anthropometric measurements were performed, and serum concentration of 25(OH)D and total alkaline phosphatase (ALP) activity were measured. Results Among the 58 patients receiving long-term AC treatment, a high proportion (46.6%) demonstrated significant vitamin D deficiency with concentrations of 25(OH)D lower than 20 ng/mL. The median concentration of 25(OH)D in subjects receiving AC was significantly lower compared to the control group [20.4 (17.4; 26.1) vs. 28.2 (24; 32.7); p < 0.001]. No differences were found between women and men receiving AC therapy. In patients receiving AC, a negative correlation was found between the concentration of 25(OH)D and the weekly dose of AC (r = −0.337, p = 0.01). Patients with concentrations of 25(OH)D < 20 ng/mL were found to have a significantly higher median dose of AC, compared to those with concentrations of 25(OH)D ≥ 20 ng/mL [21 (17; 31) vs. 17 (12; 28); p = 0.045]. Conclusion In conclusion, treatment with AC is associated with low 25-hydroxyvitamin D levels, although the path leading to this phenomenon is not entirely clear. Long-term administration of AC in adults may increase the risk of chronic vitamin D deficiency, thus, effective supplementation of vitamin D in these individuals needs careful consideration.